Molecular Typing of Somatic Coliphage Groups and Their Occurrence and Survival in Sewage - Heesuk Lee; Jeremy Chemla; Thomas A. Randall; Emily S. Bailey; Mark D. Sobsey (Applied Microbiology)
A conventional, group-specific PCR method was developed to identify each of the four previously defined major taxa (Myoviridae, Siphoviridae, Podoviridae and Microviridae) of somatic coliphages and used to classify isolates from sewage. Somatic coliphage infectivity detection, occurrence and survival in primary human sewage effluent was observed over time to further understand the presence and behavior of the groups of somatic coliphages at two environmental temperatures (4 and 25 °C). Over time, the taxonomic composition of the somatic coliphage population in sewage changed, with the Microviridae family becoming the most prevalent family in the sewage population after several weeks. Based on their persistence and prevalence in environmental waters, phages belonging to the Microviridae family provide supporting information on sewage contamination and possibly of human enteric viruses in sewage-contaminated water.